2015
DOI: 10.1038/srep17897
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Epithelium Cells from shRNA Mediated Transgenic Goat Show High Resistance to Foot and Mouth Disease Virus

Abstract: Foot and mouth disease induced by foot and mouth disease virus (FMDV) is severe threat to cloven-hoofed domestic animals. The gene 3Dpol in FMDV genome encodes the viral RNA polymerase, a vital element for FMDV replication. In this study, a conserved 3D-7414shRNA targeting FMDV-3Dpol gene was designed and injected into pronuclear embryos to produce the transgenic goats. Sixty-one goats were produced, of which, seven goats positively integrated 3D-7414shRNA. Loss of function assay demonstrated that siRNA effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The examined brain tissues of a transgenic cloned fetus from lentiviral-shRNA transfected fibroblasts showed a significant decrease in PrP expression (Golding et al, 2006). Tongue epithelium cells isolated from transgenic goats carrying shRNA against the FMDV 3Dpol gene showed effective resistance after FMDV challenge (Li et al, 2015). Moreover, ear fibroblasts isolated from transgenic lambs that carried shRNA against the FMDV- VP1 gene showed a significant inhibitory effect on the VP1 gene (Deng et al, 2017).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…The examined brain tissues of a transgenic cloned fetus from lentiviral-shRNA transfected fibroblasts showed a significant decrease in PrP expression (Golding et al, 2006). Tongue epithelium cells isolated from transgenic goats carrying shRNA against the FMDV 3Dpol gene showed effective resistance after FMDV challenge (Li et al, 2015). Moreover, ear fibroblasts isolated from transgenic lambs that carried shRNA against the FMDV- VP1 gene showed a significant inhibitory effect on the VP1 gene (Deng et al, 2017).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…Li et al have successfully produced transgenic goats that highly express 3D-7414siRNA-targeting 3D pol genes of FMDV genome. Subsequent experiments have supported the finding that tongue epithelium cells from transgenic goats effectively inhibit virus replication [46].…”
Section: Discussionmentioning
confidence: 89%
“… 35 Although it has been reported to play a regulatory role in many diseases, the role of TET1 has not been well studied in RA. 36 38 Previous evidence has shown that miR-21-5p can target TET1 in human colorectal cancer, 39 and that TET1 inactivates KLF4 in gastric cancer through a DNA methylation mechanism. 14 In this study, we showed that TET1 could promote KLF4 in mFLS cells to induce a proliferation defect and inflammatory response by remodeling the methylation status in the KLF4 promoter.…”
Section: Discussionmentioning
confidence: 99%